Shape evolution in the neutron-rich tungsten region - Stevenson, P; Brine, M; Podolyak, Z; Regan, P; Walker, P; Stone, JR (2005)
Recent experimental data on the low-lying states in W190 show a change in the E(41+)/E(21+) behavior compared to less neutron-rich neigbors. Self-consistent axially-deformed Hartree-Fock calculations, using a separable monopole interaction, of nuclei in the vicinity of W190 are performed to systematically examine the evolution of ground state quadrupole deformations. It is found that the neutron number N=116 causes a coexistence of oblate and prolate shapes, with a weak dependence on proton number, thereby hindering the development of these isotones as well-deformed rotors. © 2005 The American Physical Society.